Corrosion induced by low-energy radionuclides : modeling of tritium and its radiolytic and decay products formed in nuclear installations - Bellanger, Gilbert; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier, 2004)
Nuclear power plants emit radiation and particles across a range of energies. This radiation can cause corrosion to occur in critically important parts of the plant, which can lead to efficiency and safety problems. Gamma rays and neutrons have the highest energies and can break the metal bonds in interior metallic structures causing damage quickly and in easily monitored ways. Consequently these types of radiation and the best alloys to use to mitigate their effects have been extensively researched and their findings applied. However, the same is not true of low energy radiation which effects metal structures in a different way but can still cause appreciable and expensive corrosion. Low energy radiation degrades the passive oxide layers that protect metals. Without this protective layer the metals are easily corroded. This book uses tritium and tritiated water as models to describe the effects of low energy radiation on the corrosion of metals in these environments. Comprehensive coverage of the fields of liquid and gas flow, heat exchange, gas diffusion in materials, and of materials resistance to corrosion is ensures the reader has a full understanding of how these processes effect corrosion in nuclear installations. Such an understanding is essential for the efficient and safe running of all modern plant that uses radioactive material and this book is a critical reference tool for anyone involved in the nuclear power industry or metals research. * Unique coverage of low energy radiation and its corrosive effects in nuclear installations * Provides coverage of basic scientific principles contributing to corrosion * An essential reference for the safe and efficient construction and operation of nuclear installations * Applications in power generation, fuel reprocessing, military and civilian applications. * The first book to present detailed analysis of nuclear corrosion by low energy nuclides * The most complete book available for those serious about understanding corrosion in all its aspects * Keeping you at pace with the new methods that are changing the concept of corrosion in the nuclear industry.
effects of tritium and decay energy -- -effects of radiolytic products -- -arrangements of materials -- -remedies -- -hydrodynamic (turbulent and stagnant water) flow loops, monitoring tests integrated in the production section, with a facility for introducing corrosion inhibitors -- -designs to avoid media-induced corrosion -- -designs to avoid corrosion of alloys and stainless steels -- -corrective actions for engineers working in nuclear installations.
Includes bibliographical references (pages 501-512) and index.
Print version record.
Elsevier
Keywords: Tritium; Metals -- Corrosion fatigue; Nuclear engineering -- Safety measures; SCIENCE -- Chemistry -- Inorganic; Metals -- Corrosion fatigue; Nuclear engineering -- Safety measures; Tritium; Electronic books